A new Arctic strategy for the EU: maritime security and geopolitical signalling - Paul, Michael (DEU, 2021)
The European Union is an Arctic actor with a long record of engagement. Climate change and safeguarding the Arctic, sustainable development and international cooperation are the priority areas guiding its Arctic policy and its numerous projects in the region. Although the Union lacks formal observer status in the Arctic Council, member states Finland, Sweden and the Kingdom of Denmark are members of the body, along with Iceland and Norway, which are members of the European Economic Area and participate in the EU Framework Programme for Research and Innovation. Whereas the environmental and sustainability elements spelled out in the Commission’s communication of 2016 remain highly relevant, the region’s growing geopolitical significance makes the lack of a security policy component an increasingly pressing concern. This should therefore be addressed in the EU’s new Arctic policy, which is currently being finalised after the public consultation ended in November 2020. Maritime security offers a tested and appropriate field for expanding EU engagement. (author's abstract)